Effect of Liquidity Risk, Premium Growth on the Performance of Quoted Insurance Firms in Nigeria: A Panel Data Analysis - Olalekan, Lasisi Isiaka (American Finance & Banking Review, 2018)
This study assesses the effect of liquidity risk on firm performance of listed insurance companies in Nigeria for the period of 2011-2015. The listed insurance firms are twenty Five (25) in numbers out of which a sample of twelve (12) were used for the study. Liquidity risk as the independent variable was proxy with leverage, claim loss ratio and premium growth, while the return on asset was used to proxy firm performance. The study adopts a panel multiple regression techniques and data were collected from secondary source through the annual reports of the firms after controlling for fixed/random effects.The findings of random effect reveal that leverage has significant negative effect on return on assets. The claim loss ratio has insignificant negative influence on return on assets while premium growth has positive and insignificant effect on firm performance of listed insurance companies in Nigeria. It is recommended among others that the managers, shareholders and other stake holders to checkmate and control liquidity risk as it have been found empirically to enhance the quality of the firm’s financial performance.